Characterization of the political participation of young people. Transmedia methodological route transmedia - Burgos Videla, Carmen; Pérez, Jairo Antonio; Rey Vásquez, Elías Manaced; Roa Ovalle, Iván (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
A Polifonías as a project accounts for the political thinking of young people through transmedia narratives, it emerges from the problem of political and civic participation of young people. The methodological apparatus used was the transmedia ethnography approach. In the first stage of the study, various forms of youth participation and conceptions of politics and democracy are presented. A gamified diagnostic tool is developed that provides as a result data on the description of the sample in terms of the diverse positions of young people in relation to the exercise of politics and decision-making.